Direct Synthesis of Fluorinated Heteroarylether Bioisosteres1. Issue 14 (4th March 2013) - Zhou, Qianghui; Ruffoni, Alessandro; Gianatassio, Ryan; Fujiwara, Yuta; Sella, Eran; Shabat, Doron; Baran, Phil S.
<x xml:space="preserve">Abstract</x> (Bioiso)steering in a new direction: A modular synthesis of reagents (e.g. sodium difluoroethylsulfinate) that can be used for the direct incorporation of difluoroalkyl groups onto heterocycles is reported. The scope and generality of the incorporation of difluoroalkyl groups is exemplified with the difluoroethyl group and a proof of principle is shown for a general synthesis of fluorinated heteroarylether bioisosteres.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>